Atmospheric stability above 6-m Big Telescope Alt-Azimuthal site - Bolbasova, Lidia A. (Proceedings of SPIE)
The high-altitude distributions of the Richardson number above the 6-meters Big Telescope Alt-Azimuthal of SAO RAS for astronomical site characterization are study. The 1/Ri used as parameter for ranking sites in term regime of stability and relative probability of periods and regions of turbulence. The profiles of the gradients of the potential temperature and the wind speed up to height of 25km for each month of year are calculated. The data used from the ERA-Erratum reanalysis, which is widely acknowledged as being reliable